From variant of uncertain significance to likely pathogenic in two siblings with atypical RAG2 Deficiency: a case report and review of the literature - Nima Taghizadeh Mortezaei; Soha Mohammadi; Hassan Abolhassani; Sima Shokri; Mohammad Nabavi; Morteza Fallahpour; Mohammad Hassan Bemanian (BMC, 2024)
Abstract Background Severe combined immunodeficiencies (SCIDs) are hereditary disorders characterized by impaired T and B cell function, resulting in significant immune system dysfunction. Recombination-activating gene (RAG) mutations account for a substantial proportion of SCID cases. Here, we present two sibling cases of SCID caused by a novel RAG2 gene mutation. Case Presentation The index case was an 8-year-old boy who had a history of recurring infections. After a comprehensive immunological workup, the initial diagnosis of agammaglobulinemia was revised to combined immunodeficiency (CID). The patient underwent hematopoietic stem cell transplantation (HSCT) but succumbed to cytomegalovirus (CMV) infection. His brother, a 4-month-old boy, presented with CMV chorioretinitis. Leaky SCID was diagnosed based on genetic tests and immunological findings. The patient received appropriate treatment and was considered for HSCT. Both siblings had a homozygous RAG2 gene variant, with the first case classified as a variant of uncertain significance (VUS). The presence of the same mutation in the second brother, and the clinical phenotype, supports considering the mutation as likely pathogenic. Conclusions This case report highlights a novel RAG2 gene mutation associated with CID. The classification of a VUS may evolve with accumulating evidence, and additional studies are warranted to establish its pathogenicity. Proper communication between genetic counselors and immunologists, accurate documentation of patient information, increased public awareness, and precise utilization of genetic techniques are essential for optimal patient management.